2020
DOI: 10.1093/nar/gkaa684
|View full text |Cite
|
Sign up to set email alerts
|

METTL4 catalyzes m6Am methylation in U2 snRNA to regulate pre-mRNA splicing

Abstract: N 6-methylation of 2′-O-methyladenosine (Am) in RNA occurs in eukaryotic cells to generate N6,2′-O-dimethyladenosine (m6Am). Identification of the methyltransferase responsible for m6Am catalysis has accelerated studies on the function of m6Am in RNA processing. While m6Am is generally found in the first transcribed nucleotide of mRNAs, the modification is also found internally within U2 snRNA. However, the writer required for catalyzing internal m6Am formation had remained elusive. By sequencing transcriptome… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 65 publications
0
52
0
Order By: Relevance
“…Additionally, the level of base methylation could also be severely reduced when changing the 5' and 3' nucleotides, pointing toward sequence recognition by the METTL4. In an independent study, Goh et al (2020) confirmed METTL4 as the enzyme responsible for the m 6 Am30 modification (with Am being the true substrate). The authors also confirmed the base modification identity with HPLC-MS/MS ( Goh et al, 2020 ).…”
Section: Modified Nucleotides In Spliceosomal Snrnasmentioning
confidence: 84%
See 2 more Smart Citations
“…Additionally, the level of base methylation could also be severely reduced when changing the 5' and 3' nucleotides, pointing toward sequence recognition by the METTL4. In an independent study, Goh et al (2020) confirmed METTL4 as the enzyme responsible for the m 6 Am30 modification (with Am being the true substrate). The authors also confirmed the base modification identity with HPLC-MS/MS ( Goh et al, 2020 ).…”
Section: Modified Nucleotides In Spliceosomal Snrnasmentioning
confidence: 84%
“…In an independent study, Goh et al (2020) confirmed METTL4 as the enzyme responsible for the m 6 Am30 modification (with Am being the true substrate). The authors also confirmed the base modification identity with HPLC-MS/MS ( Goh et al, 2020 ). Using transcriptome-wide sequencing, they further showed that this modified nucleotide contributed to splicing regulation.…”
Section: Modified Nucleotides In Spliceosomal Snrnasmentioning
confidence: 84%
See 1 more Smart Citation
“…The m 6 Am MTase was previously purified with a molecular weight of~65 KD in 1978, and phosphorylated CTD-interacting factor 1 (PCIF1) was recognized as the first m 6 Am MTase in 2019. It was named by its ability to directly bind to the phosphorylated carboxylterminal domain (CTD) of RNA polymerase II (RNAP II) by its WW domain, also called cap-specific adenosine methyltransferase (CAPAM) (106,112,113). Unlike the m 6 A core readers that work in the form of a methyltransferase complex, PCIF1 is a "stand-alone" RNA MTase and functions in an m 7 G cap-dependent manner.…”
Section: Components Of M 6 Am Modification System Writermentioning
confidence: 99%
“…N6methyladenosine (m 6 A) modification refers to the addition or deletion of the methyl group to/from the nitrogen on the 6th carbon of the adenine nucleotide, which is one of the most abundant epigenetic modifications found in RNA molecules (13). First discovered by Desrosiers in the 1970s, m 6 A modification has been found to be involved in almost all steps of RNA processing and metabolism, including pre-mRNA splicing, export, translation, stabilization, and degradation (14)(15)(16)(17)(18)(19). With the burgeoning advances in molecular biology and sequencing, m 6 A modification has been reported to be implicated in virtually all cellular functions and multiple diseases (including osteosarcoma) (20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%